Does Agroindustry Accelerate Convergence of Economic Growth in East Java? - Santoso, Dwi Budi (Jurnal Ekonomi Kuantitatif Terapan, 2023)
In most areas of East Java, the economic development still relies on the agricultural sector.  Meanwihle, since 2008, agroindustry has grown fast in East Java. This situation should have impact towards higher economic growth in lieu with lower regional development disparity, or speed of convergence improvment. However, the reality seems to be different, where the level of regional development inequality in East Java is still far above the National level. Thus, this study aims to estimate the magnitude of agroindustry in the acceleration of convergence in East Java. This study uses least squares and spatial models as estimation methods as well as the Barro convergence model as the basis of model analysis. The data used is panel data from 38 regions from 2010 to 2019. The estimation results show that agroindustry development has played a role in accelerating convergence improvement, but not too big. One reason is that there is still no spillover effect arising from agroindustry development.